Reading Reception Selected Surahs: A Study of Living Qur'an in Subulussalam Islamic Boarding School Weding, Bonang, Demak - Salma Robiatul Adawiyah; Jaka Ghianovan; Abil Ash (JIA (Jurnal Ilmu Agama), 2025)
This research discusses the phenomenon of Living Qur'an that occurs in the community, namely the tradition of reading Surah Ash-Shams, al-Lail, al-Mu'awwidzatain, al-Baqarah verse 255, and al-Baqarah verse 285-286, in Subulussalam Weding Islamic Boarding School, Bonang, Demak Regency. The objectives in this study are: First, to know the origin of the tradition of reciting Surah Ash-Shams, al-Lail, al-Mu'awwidzatain, al-Baqarah verse 255, and al-Baqarah verse 285-286 in Subulussalam Weding Islamic Boarding School, Bonang, Demak Regency. Second, to find out the reception of pesantren residents towards the recitation of Surah Ash-Shams, al-Lail, al-Mu'awwidzatain, al-Baqarah verse 255, and al-Baqarah verse 285-286 in Subulussalam Weding Islamic Boarding School, Bonang, Demak Kab. This activity was attended by all santri, administrators, and ustadzah which was held every afternoon before maghrib. This type of research is field research using qualitative methods and a sociology of knowledge approach. Through observation, interview, and documentation techniques, this research will explain how this tradition began and the reader's reception of Surah Ash-Shams, al-Lail, al-Mu'awwidzatain, al-Baqarah verse 255, and al-Baqarah verse 285-286, in Subulussalam Weding Islamic Boarding School, Bonang, Demak Regency. Based on the analysis that has been done, researchers found two points of findings, namely: First, the evidence used is the Qur'anic verse of Surah Thaha verse 130 and the book of Maraqil Ubudiyah pp. 38 by Syaikh Nawawi al-Bantani. Second, the pesantren residents' receptions of this tradition are to facilitate memorization, launch fortune, facilitate affairs and for the happiness of the world and the hereafter. This article contributes to enriching the study of Living Qur'an by preserving the tradition of reciting Surah Ash-Shams, al-Lail, al-Mu'awwidzatain, al-Baqarah verse 255, and al-Baqarah verse 285-286, in Subulussalam Weding Islamic Boarding School, Bonang, Demak Regency.